Tokoh Sentral Dalam Kodifikasi Hadis - Junaid bin Junaid (LPPM IAIN Sorong, 2022)
Hadith codification is an umbrella for understanding the beginning of the book of the Prophet's hadith. and this is of course urgent in it is to talk about history. Because it itself is departing from past, present and future events. History gives its own meaning in codifying the hadith of the Prophet Muhammad. because in this event it is not necessarily recorded in a book of hadith. But through a process that departs from the pre-codification of the hadith. One of the pre-codifications is how the hadith of the Prophet saw is recorded and written in the form of sahifah. In the codification of the hadith, there are three important main figures who can serve as aspirations in developing and maintaining the hadith of the Prophet Muhammad. ulumul hadith. Because with the codification of the hadith, the history of the prophet's hadith can be understood objectively. Therefore, understanding the hadith of the Prophet saw should not only look at it from one point of view. Because it will create a subjective understanding and will give rise to a conflict that will end with a hatred, so that fellow Muslims themselves have quarrels that can be prolonged. And this is the urgency of understanding the meaning of history